2014
DOI: 10.1186/s12931-014-0151-9
|View full text |Cite
|
Sign up to set email alerts
|

Delay of airway epithelial wound repair in COPD is associated with airflow obstruction severity

Abstract: BackgroundAirway epithelium integrity is essential to maintain its role of mechanical and functional barrier. Recurrent epithelial injuries require a complex mechanism of repair to restore its integrity. In chronic obstructive pulmonary disease (COPD), an abnormal airway epithelial repair may participate in airway remodeling. The objective was to determine if airway epithelial wound repair of airway epithelium is abnormal in COPD.MethodsPatients scheduled for lung resection were prospectively recruited. Demogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
50
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(56 citation statements)
references
References 24 publications
6
50
0
Order By: Relevance
“…The situation in severe COPD may be very different from the relative early stage, in which the repairing ability of BCs may be relative conserved. As Perotin et al reported that delayed rather than enhanced epithelial wound repair was found in severe COPD [42]. Actually, we agree with this idea.…”
Section: Discussionsupporting
confidence: 90%
“…The situation in severe COPD may be very different from the relative early stage, in which the repairing ability of BCs may be relative conserved. As Perotin et al reported that delayed rather than enhanced epithelial wound repair was found in severe COPD [42]. Actually, we agree with this idea.…”
Section: Discussionsupporting
confidence: 90%
“…This mechanism may be impaired in COPD, since previous studies have reported attenuated Nrf2-dependent antioxidant responses in the bronchial tissues from COPD patients compared to non-COPD smokers [27, 28]. Moreover, it has been shown that COPD airway epithelial cells display reduced wound repair and epithelial barrier properties [29, 30]. Therefore, it can be speculated that an impaired oxidative stress response is related to epithelial dysfunction during COPD disease progression.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical assessment and pulmonary function tests were performed. Emphysema quantification on the resected lobe was performed visually on thoracic computed tomography scan by two independent investigators as previously described [8,9]. Formalin-fixed paraffin-embedded (FFPE) lung tissues distant from the tumour were stained with haematoxylin and eosin for bronchial epithelium analysis.…”
mentioning
confidence: 99%